The concept, transformation logic, practical dilemmas, and countermeasures in promoting the transformation of smart-empowered older adult care services via New Quality Productive Forces - Fu, Liping; Li, Meng; He, Lanping; Fang, Ya’nan (Frontiers in Public Health, 2025)
Digitization is gradually becoming integrated into the living contexts of older adults, especially in China. The New Quality Productive Forces (NQPF), one of the tools for the promotion of digitalization, is the key driver in promoting the digital transformation of older adult care services. Through the extensive review, this study analyzes the effects of NQPF on the development of smart-empowered older adult care service systems. The results reveal that the digital transformation of older adult care services is driven by the interactive effects of scientific and technological innovations, digital cognition, and the service systems. In addition, the transformation logic reveals how the older adult care industry upgrades through a multi-subject coordinated model of the supply-and-demand dimensions under New Quality Productive Forces. This study offers valuable references and insights into the transformation of digital older adult care services.